215 PREDICTORS OF RECURRENT CEREBRAL ISCHEMIA AFTER PATENT FORAMEN OVALE CLOSURE: A SINGLE CENTER OBSERVATIONAL STUDY. (15th December 2022) - De Gregorio, Mattia; Gurgoglione, Filippo Luca; Vignali, Luigi; Cattabiani, Maria Alberta; Solinas, Emilia; Benatti, Giorgio; Tadonio, Iacopo; Barocelli, Federico; Tuttolomondo, Domenico; Indrigo, Elia; Signoretta, Gianluca; Ardissino, Diego; et al.
Abstract: Background: Transcatheter patent foramen ovale (PFO) closure is an effective therapy in patients with cryptogenic stroke (CS) or transient ischemic attack (TIA) and evidence of PFO. However, the incidence of recurrent cerebral ischemia is not negligible and underlying pathogenic mechanisms remain largely unknown. We sought to evaluate the magnitude of the problem and to assess predictors of recurrent stroke/TIA after transcatheter PFO closure. Methods: We enrolled non-randomized consecutive patients who underwent PFO closure for secondary prevention of neurological ischemic events at the University Hospital of Parma between 2004 and 2021. Clinical, echocardiographic and procedure-related features were collected for each patient. The incidence of recurrent ischemic neurological events was assessed at follow-up. Results: We enrolled a total of 154 patients. The primary indication for PFO closure was previous stroke (85 [55.2%] subjects) and a third of patients (51 [33.1%]) suffered from migraine, 22 [14.3%] with and 29 [18.8%] without aura. Moreover, mean Risk of Paradoxycal Embolism (ROPE) score at hospital admission was 6.4 ± 1.5. After a median follow-up of 112 months, the incidence of recurrent cerebral ischemia occurred in 13 [8.4%] patients, with an annualized rate of 0.92/100 patients. The presence of migraine, obesity and ROPE < 7 were independent positive predictors of recurrent stroke/TIA. Conclusion: The presence of obesity, a familiar history of CVD, ROPE < 7 and migraine were independent positive predictors of recurrent ischemic neurological events after PFO closure.